(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The present article aims to report an experience in Analytical-Behavioral Therapy (CAT) with a case of an university student diagnosed with major depressive disorder with psychotic characteristics and recurrent episodes, linked to anxious symptoms and identified with academic giftedness. The reported psychotherapeutic follow-up lasted three years, in a total of 101 sessions held from the perspective of behavior analysis. Social skills training, and behavioral activation tasks proved to be effective in the case, in addition to sessions aimed at working on perfectionism and functional analysis related to the diverse symptoms. Among the results, a reduction in the frequency of anxious and depressive crises were identified, in addition to improvement in interpersonal relationships and coping in face of social situations that were previously costly. The study indicates evaluation losses and standardized procedures for cases of comorbidities and the importance of evidence-based practice in the study of these cases.